Meningkatkan proses dan hasil belajar matematika siswa pada materi persamaan linier dua variabel melalui model pembelajaran Think Talk Write (TTW) - Sri Wahyuningsih (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This research aim to (1) describe the achievement of the implementation of Think Talk Write (TTW) Learning Model, (2) Increasing student activity (3) Student learning outcomes, and (4) Describing student responses to Think Talk Write (TTW) Learning Model in the material Two Variable Linear Equations. The results showed that (1) the implementation of the Think Talk Write (TTW) Learning Model in the Two-Variable Linear Equation material was carried out by the teacher entirely from 80.77% in the first cycle, 96.15% in the second cycle, experiencing a 100% increase in the cycle III with criteria very high, (2) Student activity 49.75% in the first cycle, 75.75% in the second cycle experienced an increase in the third cycle of 91.50% with a very active criteria, (3) Student learning outcomes in the two-variable linear equation material after using the model Think Talk Write (TTW) learning shows the existencean increase from 66.40 in the first cycle, 72.15 in the second cycle to 83.55 in the third cycle with classical completeness of 55%, 70% and 100% respectively. (4) responses of 95% students stated that they were very happy to learn the material of two-variable linear equations using the learning modelThink Talk Write (TTW).so that it can be concluded that the Think Talk Write (TTW) Learning Model can improve the process and results of mathematics learning in class VIIIA Pelaihari SMP Negeri 6 in the Two Variable Linear Equation Material.